Chromium removal by zeolite-rich materials obtained from an exhausted FCC catalyst: Influence of chromium incorporation on the sorbent structure - González, Maximiliano (2013)
A spent FCC catalyst was converted into a zeolitic mixture, and the product obtained was afterward used as trapping material for Cr(III) species frequently found in aqueous solutions. Eventual changes in the sorbent structure produced by Cr incorporation were studied by different characterization techniques such as point of zero charge determinations (PZC), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), and infrared absorption (FTIR). The XRD and FTIR analyses indicated that chromium incorporation produces an amorphization of the material, and PZC measurements show no surface adsorption of charged chromium species. SEM and EDX analyses clearly show that after chromium sorption, the initial microspheroidal catalyst morphology was maintained, and the presence of chromium species was mainly detected in the outer microsphere surface, where the zeolite crystals were hydrothermally grown.